Africanismos en el español de México - Lara, Luis Fernando (El Colegio de México, 2015)
First of all a summary is made of all that is presently known about African slavery in Latin America, and especially in Mexico, from the 16th century onwards, whilst mention is also made of the different hypotheses relating to the existence of a generalized Afro-Portuguese Pidgin or Creole language. The way in which the Africans were assimilated into New Spain is then examined, particular attention being paid to the differences between this region and other regions of Latin America. The influence of African languages in Mexican Spanish is shown to be limited to the vocabulary, and more precisely to place-names and every day expressions. A list of these words is offered, together with a discussion of their etymology.